Does Fracture Pattern Influence Functional Outcomes in the Management of Bilateral Mandibular Condylar Injuries?. Issue 3 (September 2019) - Wang, Howard D.; Susarla, Srinivas M.; Yang, Robin; Mundinger, Gerhard S.; Schultz, Benjamin D.; Banda, Abhishake; MacMillan, Alexandra; Manson, Paul N.; Nam, Arthur J.; Dorafshar, Amir H.
The purpose of this study was to compare the functional outcomes of different types of bilateral mandibular condylar fractures. This was a retrospective study of patients with bilateral mandibular condylar fractures at a level-1 trauma center over a 15-year period. The primary predictor variable was fracture pattern, classified as type I (bilateral condylar), type II (condylar–subcondylar), or type III (bilateral subcondylar). Secondary predictor variables were demographic, injury-related, and treatment factors. Bivariate associations between the predictors and complication rates were computed; a multiple logistic regression model was utilized to adjust for confounders and effect modifiers. Thirty-eight subjects with bilateral condylar injuries met the inclusion criteria. The sample's mean age was 37.6 + 18.2 years, and 16% were female. The most common mechanisms of injury were motor vehicle collisions (53%) and falls (29%). Seventy-four percent had associated noncondylar mandibular fractures, and 32% of cases had concomitant midface fractures. Fifty-three percent of cases were classified as type I, 21% as type II, and 26% as type III. Ten subjects (26%) were managed with open reduction and internal fixation. The average length of follow-up was 4.5 + 6.3 months. After adjusting for confounders and effect modifiers, the type of fracture was a significant predictor of functional complications with type II injuries having the highest likelihood of a poor functional outcome (odds ratio: 7.77, 95% confidence interval: 1.45–41.53, p = 0.02). Asymmetric bilateral mandibular condylar fractures may be associated with an increased risk of poor functional outcomes.